CIMA Fundamentals of Business Economics (BA1) Exam Kit 2022 - Kaplan Publishing (Berkshire Kaplan Publishing, 2022)
The Fundamentals of Business Economics Exam Kit complements the Study Text, with exam-style questions that cover the fundamentals of business economics. You'll strengthen your understanding of the evaluation and forecasting the behaviour of consumers. Included is paper-specific information, exam technique, and our recommended revision approach.
Keywords: Macroeconomic and Institutional Context of Business; Microeconomic and Organisational Context of Business; Informational Context of Business; Financial Context of Business; Nonfiction